1997
DOI: 10.1023/a:1008278605751
|View full text |Cite
|
Sign up to set email alerts
|

Intensive therapy with peripheral stem cell transplantation in 16 patients with mantle cell lymphoma

Abstract: In this study we were not able to confirm the hypothetical benefit of high-dose chemotherapy and PBSC transplantation in mantle cell lymphoma, even though this approach may be promising in a subgroup of patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 13 publications
1
28
0
Order By: Relevance
“…Among these 19 patients, nine were in continued CR with a median follow-up of almost 3 years. Apart from the report of Ketterer et al, 19 all published series have shown a high complete response rate after transplantation. This result demonstrates the possibility of effecting complete resolutions of the disease with therapeutic intensification.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Among these 19 patients, nine were in continued CR with a median follow-up of almost 3 years. Apart from the report of Ketterer et al, 19 all published series have shown a high complete response rate after transplantation. This result demonstrates the possibility of effecting complete resolutions of the disease with therapeutic intensification.…”
Section: Discussionmentioning
confidence: 90%
“…Very few studies, 13,19,20,22 have confirmed that the diagnosis of MCL was based on up-to-date published criteria of the REAL or WHO classifications. Histopathological review therefore confers a more realistic value on our work in terms of defining the efficacy of therapeutic intensification for mantle cell lymphomas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The published series are mostly retrospective, and have included patient populations which are heterogeneous with respect to extent and nature of prior therapy, status at the time of SCT, type of high-dose regimen, source of stem cells and ex vivo manipulation of stem cell products. [1][2][3][4][5][6][7][8][9][10][11]40,41 In addition, some retrospective studies have not included central histologic review. Reproducible diagnostic criteria for MCL have only recently been established and the consistency of diagnosis for MCL without modern diagnostic techniques is poor.…”
Section: Results Of High-dose Therapy and Autologous Stem Cell Transpmentioning
confidence: 99%
“…A total of 287 autologous transplants for MCL have been reported to the Autologous Blood and Marrow Transplant Registry of North America (ABMTR) since 1990, 177 of which have been performed since 1998. An increasing number of single institution and registry-based studies of SCT for MCL have been reported over the last 5 years, [1][2][3][4][5][6][7][8][9][10][11] and early reports of allogeneic SCT have also been published recently. [12][13][14][15] The number of cases reported in publications or to registries probably represents only a fraction of the total number of transplant procedures being performed for this disease.…”
mentioning
confidence: 99%